Propagation of microcracks in collagen networks of cartilage under mechanical loads. Issue 9 (September 2019) - Santos, S.; Emery, N.; Neu, C.P.; Pierce, D.M.
Summary: Objective: We recently demonstrated that low-energy mechanical impact to articular cartilage, usually considered non-injurious, can in fact cause microscale cracks (widths < 30 μ m) in the collagen network of visually pristine human cartilage. While research on macro-scale cracks in cartilage and microcracks in bone abounds, how microcracks within cartilage initiate and propagate remains unknown. We quantified the extent to which microcracks initiate and propagate in the collagen network during mechanical loading representative of normal activities. Design: We tested 76 full-thickness, cylindrical osteochondral plugs. We imaged untreated specimens (pristine phase) via second harmonic generation and assigned specimens to three low-energy impact groups (none, low, high), and thereafter to three cyclic compression groups (none, low, high) which simulate walking. We re-imaged specimens in the post-impact and post-cyclic compression phases to identify and track microcracks. Results: Microcracks in the network of collagen did not present in untreated controls but did initiate and propagate under mechanical treatments. We found that the length and width of microcracks increased from post-impact to post-cyclic compression in tracked microcracks, but neither depth nor angle presented statistically significant differences. Conclusions: The microcracks we initiated under low-energy impact loading increased in length and width during subsequent cyclic compression that simulated walking. The extent of this propagation depended on the combination of impact and cyclic compression. More broadly, the initiation and propagation of microcracks may characterize pathogenesis of osteoarthritis, and may suggest therapeutic targets for future studies.